2018
DOI: 10.1111/medu.13674
|View full text |Cite
|
Sign up to set email alerts
|

Research environments: can the cloud supplement bricks and mortar?

Abstract: While local research environments significantly impact individuals’ abilities to engage in scholarly activities, we contend that health professions education scholars are increasingly mobilizing virtual spaces and resources to further their research endeavors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…e application of new technologies such as computer technology, information technology, and network technology has given a more positive development to the prospects of higher education [3,4]. rough the survey, it is found that the application of most of the network platforms of colleges and universities is relatively single, and most of the network platforms have become educational affairs' platforms or network library platforms of major universities, and the teaching tasks are not completed as expected [5]. From the current technical point of view and teaching task requirements, it is not feasible to completely use the Internet teaching platform to replace manual teaching [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…e application of new technologies such as computer technology, information technology, and network technology has given a more positive development to the prospects of higher education [3,4]. rough the survey, it is found that the application of most of the network platforms of colleges and universities is relatively single, and most of the network platforms have become educational affairs' platforms or network library platforms of major universities, and the teaching tasks are not completed as expected [5]. From the current technical point of view and teaching task requirements, it is not feasible to completely use the Internet teaching platform to replace manual teaching [6,7].…”
Section: Introductionmentioning
confidence: 99%